Replaceable Lawyers and Guilty Defendants - Talbot, Brian (Journal of moral philosophy, 2017)
Many criminal lawyers should expect that, were they to not defend a certain client, someone no less capable would do so. It is morally wrong for such attorneys to defend defendants who should be punished. This is true even if we grant that the defendant’s right to be defended outweighs any rights that might be infringed by the defense and that the benefits of defending are greater than the harm. Nor does this argument depend on any particular view of punishment. The fact that the attorney expects to be replaced by someone equally capable has an asymmetric effect on the reasons for and against defending. The reasons that justify defending become extremely attenuated by this expectation, no matter what they are, while the reasons against defending are much less affected, no matter what they are.